PERSONAL CONTRIBUTIONS TO THE DEVELOPMENT OF THE PSYCHO-MOTOR SKILLS IN THE FOOTBALL GOALKEEPERS OF THE SPORTS HIGH-SCHOOL OF BACAU, ROMANIA (Fiep Bulletin - online, 2017)
This research aims to bring some personal contributions to the development of the psycho-motor skills in the footballgoalkeepers of the sports high-school of Bacau, Romania, with the help of several specific action means with the purpose ofimproving the training methods for the goalkeeper position, in order to bring them as close as possible to the modern, currenttechnical-tactical methods for the players that are specialized in this position.The actual experiment was conducted between May and August, 2016, on football goalkeepers of the Bacau SportsHigh School.The group of subjects that the research was focused on had initially a good level of motor skills, a good physicaltraining, but a medium-level technical training. Nevertheless, the authors of this study believed it was necessary to use morecomplex action means, considering especially the good general motor skills and the fact that the subjects could handle the drillsphysically, aiming to improve their technique and the psycho-motor skills that are specific to this position.At the beginning of the experiment, a series of action means were established for the specific goalkeeper training,common means for all the research subjects. In elaborating the action means, the authors started from the study of the gametasks of the goalkeeper during a competition game. After analyzing the goalkeeper's game from a technical-tactical point of view,according to the tasks of this position during a game, a conclusion was reached - that the specific goalkeeper training must usemeans that would develop certain psycho-motor skills that are specific to this position.At the end of the experiment and after the analysis of the results, it can be said that, through the use of the actionmeans presented in this paper, the specific goalkeeper psycho-motor skills were improved.This improvement was possible also due to the increase in the number of individualized specific goalkeeper trainingsessions
Keywords: development; psycho-motor skills; football; goalkeeper